Novel mechanism of regulation of the 5-lipoxygenase/leukotriene B4 pathway by high-density lipoprotein in macrophages - Shigeyasu Tsuda (Nature Portfolio, 2017)
Abstract High-density lipoprotein (HDL) interacts with various cells, particularly macrophages, in functional cell-HDL interactions. Here, we found that HDL protein quality and lipid quality play critical roles in HDL functions. HDL fractions from healthy volunteers (HDLHealthy) and patients with recurrent coronary atherosclerotic disease (HDLCAD) were prepared. To analyse functional HDL-macrophage interactions, macrophages were co-incubated with each HDL, and lipid mediator production was assessed by liquid chromatography/mass spectrometry-based metabololipidomics. HDLHealthy treatment attenuated the pro-inflammatory lipid mediator production, particularly that of leukotriene (LT) B4, and this treatment enhanced lipoxin (LX) B4 and resolvin (Rv) E2 production. HDLHealthy treatment enhanced the proteasome-mediated degradation of the LTB4-producing enzyme 5-lipoxygenase (LO) in activated macrophages; however, HDLCAD did not show these anti-inflammatory effects. HDLHealthy was engulfed by macrophages via clathrin-mediated endocytosis, which was a critical step in 5-LO/LTB4 regulation. We also found that HDLCAD showed higher levels of the LTB4-producing enzymes and thus promoted LTB4 production from HDLCAD. In addition, LTB4 attenuated HDL endocytosis, HDL-mediated 5-LO degradation in macrophages, and HDL-derived augmentation of macrophage phagocytosis. These results indicated that local LTB4 produced de novo from HDLCAD regulates HDL-macrophage functional interactions and plays critical roles in dysfunctional, inflammatory HDL characteristics.